Front Cover: Supramolecular Self‐Assembly of DNA with a Cationic Polythiophene: From Polyplexes to Fibers (ChemNanoMat 6/2019). Issue 6 (22nd May 2019) - Leclercq, Maxime; Rubio‐Magnieto, Jenifer; Mohammed, Danahe; Gabriele, Sylvain; Leclercq, Laurent; Cottet, Hervé; Richeter, Sébastien; Clément, Sébastien; Surin, Mathieu
Abstract : Cationic polythiophenes (CPTs) constitute an interesting class of π‐conjugated polymers for DNA sensing and delivery. Here, the supramolecular self‐assembly of a poly[3‐(6'‐(trimethylphosphonium)hexyl)thiophene‐2, 5‐diyl] and various types of DNA is explored. In aqueous solutions, polyplex formation occurs with hydrodynamic radii between a few nm to around 25 nm. Chirality induction occurs from DNA to the achiral polymer, with important chiroptical signals in the spectral range of the latter. When solutions are deposited on surfaces, aggregation yield long dendritic fibers that can extend over tens μm with long DNA yield long fiber, with homogeneous fluorescence of the polymer. More information can be found in the Communication by Hervé Cottet, Sébastien Clément, Mathieu Surin et al. onpage 703 in Issue 6, 2019 (DOI:10.1002/cnma.201900022 ).